The Final Victory for the Barbarians? - Vermoortel, Philip (Werkwinkel, 2016)
In 1860 the Dutch author Multatuli (pen name of Eduard Douwes Dekker) published Max Havelaar, which was to become the most famous 19th century Dutch novel. In 2010 the book was rewritten by NRC-journalist Gijsbert van Es. His purpose was to make the book more accessible for secondary school pupils for whom Max Havelaar was on the mandatory reading list. He modernized the language, updated the vocabulary but also cut out a number of long-winded passages, making the 2010 version about one fifth shorter than the original. This article analyses the many reactions to the adaptation, going from lavish praise to complete disapproval. The article focuses on the arguments of advocates and opponents, evaluating their validity. It also tries to answer the question whether the author has achieved his aim.